Treaties in motion : the evolution of treaties from formation to termination / Malgosia Fitzmaurice, Panos Merkouris. - Fitzmaurice, Malgosia, 1957-; Merkouris, Panos (Cambridge studies in international and comparative law ;, 2020)
The law of treaties is in constant motion, understood not only as locomotion, but also as motion through time and as change. Thus, kinesis and stasis, two sides of the same concept of 'motion', are the central themes of Treaties in Motion. The concept of motion adopted in this book is based on the philosophy of Aristotle. He identified six types of motion: creation (genesis), increase (auxesis), diminution (meiosis), alteration (alloiosis), destruction (phthora), and change of place (kata topon metabole), which has been amended by the authors to change in space-time (kata topon kai chronon metavole) to reflect our modern scientific understanding of time as a dimension through which motion and change occurs. Each chapter's analysis proceeds by focusing on a specific area of a treaty's 'life-cycle', where each type of motion shines through and is described through three different frames of reference: treaties, the Vienna Convention of the Law of Treaties, and customary law.